The wrong thing to do is nothing [sound recording] - Hubbard, L. Ron (La Fayette Ron) 1911-1986 (Los Angeles, California Golden Era Productions, 2009)
Lecture on why people should try to change life on Earth for the better, especially given the invention of nuclear weapons.
Digital recording.
An L. Ron Hubbard Classic Lecture.
A lecture given on the 17th of November 1954 with transcripts and glossary and a guide with related issues.
Lectured by L. Ron Hubbard.
Recorded with Clear sound, State of the Art Sound Technology®.
Keywords: International Association of Scientologists; Scientology; Audiobooks